The Effect of Pupil Size on Stimulation of the Melanopsin Containing Retinal Ganglion Cells, as Evaluated by Monochromatic Pupillometry - Nissen, Claus; Sander, Birgit (Frontiers in Neurology, 2012)
Purpose. To evaluate the influence of the size of the light exposed pupil in one eye on the pupillary light reflex of the other eye. Method. Using a monochromatic pupillometer, the left eye in each of 10 healthy subjects was exposed to 20 s of monochromatic light of luminance 300 cd/m2, first red (660 nm) and in a following session, blue (470 nm) light. The consensual pupillary diameter in the right eye was continuously measured before, during and after light exposure. Subsequently, Tropicamide 1% or Pilocarpine 2% was instilled into the left eye and when the pupil was either maximally dilated or contracted, the entire sequence of red and blue light exposure repeated. After at least three days, when the effect of the eye drop had subsided, the entire experiment was repeated, this time employing the other substance. Results. Prior dilatation of the left pupil augmented the post light contraction to blue (p<0.0001), but not to red light. The contraction during light exposure did not change. Prior contraction of the left pupil decreased the post-stimulus contraction to blue light (p<0.04). Conclusion. The size of the light exposed pupil influences the magnitude of the response to blue, but not to red light. Prior dilatation may therefore prove useful, when the response to blue light - as a marker of melanopsin containing retinal ganglion cell function - is of interest, especially when this response is weak.